2017
DOI: 10.2174/1381612823666170329125820
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with HIV Testing and HIV Treatment Adherence: A Systematic Review

Abstract: The identification of persons who are less likely to test for HIV, and to adhere to HIV treatment, may serve as a guide for public health interventions, especially in resource-limited areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 0 publications
0
26
0
2
Order By: Relevance
“…Although along with the widely use of ART treatment, people have realized that HIV/AIDS can be manageable as a type of chronic disease, the collective memories and stories of AIDS patients in the past several decades have been so painful that the knowledge burden of HIV diagnosis may overweigh the benefits of early treatment [ 16 , 43 ]. In addition, social support is found to be an important facilitator for the linkage to HIV treatment cascade [ 44 , 45 ]. These factors need to be addressed in social mobilization strategies for HIV-testing promotion [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although along with the widely use of ART treatment, people have realized that HIV/AIDS can be manageable as a type of chronic disease, the collective memories and stories of AIDS patients in the past several decades have been so painful that the knowledge burden of HIV diagnosis may overweigh the benefits of early treatment [ 16 , 43 ]. In addition, social support is found to be an important facilitator for the linkage to HIV treatment cascade [ 44 , 45 ]. These factors need to be addressed in social mobilization strategies for HIV-testing promotion [ 44 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, social support is found to be an important facilitator for the linkage to HIV treatment cascade [ 44 , 45 ]. These factors need to be addressed in social mobilization strategies for HIV-testing promotion [ 44 , 46 ]. Health facilities can also modify their arrangement of schedule, site location, and environment of HIV-testing clinics to improve their convenience, confidentiality and accessibility.…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy consisted of combined search queries of keywords related to HIV/AIDS and keywords related to medication adherence. Keywords used were partially obtained from previously published literature on AIDS-related medication adherence [ 21 , 23 , 45 , 46 ]. An exclusion step was implemented to eliminate potential false positive documents.…”
Section: Methodsmentioning
confidence: 99%
“…The independent variables were selected and grouped based on three reasons: first, conclusion from previous studies (11,12,14,18,19,37,40,41) that have found them to have an association with HIV testing among men; second, the conceptual framework ( Figure 1); and finally, their availability in the 2014 GDHS dataset.…”
Section: Independent Variablesmentioning
confidence: 99%